2009
DOI: 10.1007/s10661-009-0881-1
|View full text |Cite
|
Sign up to set email alerts
|

Observational and modeling study of dry deposition on surrogate surfaces in a South China city: implication of removal of atmospheric crustal particles

Abstract: Dry deposition samples collected during 1999-2001 at a South China site using surrogate surfaces were analyzed by capillary electrophoresis. Collector surface properties played important roles to the dry deposition. The deposition velocities for various species ranged from 0.02 to 1.69 cm s(-1), in general agreement with literature values. More than 90% of Ca(2+) was deposited by sedimentation and its comparable values of dry or wet removal residence times imply that dry deposition is an important atmospheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Dry deposition is calculated by multiplying the area of the Tolo Harbor, deposition velocity of aerosols, the nutrient concentrations in aerosols, and the solubility of each nutrient, while wet deposition is estimated by multiplying the area of the Tolo Harbor, precipitation rate, and nutrient concentrations in the rainwater. The dry deposition velocities for NH 4 + and NO x − in Tolo Harbor area are 0.03 and 0.12 cm/s, respectively (Wai et al, ). The concentrations of NH 4 + and NO x − in aerosols of Hong Kong are ~ 3042.2 ± 438.7 and 3781 ± 415.4 ng/m 3 according to the data from 2010 to 2016 (EPD, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dry deposition is calculated by multiplying the area of the Tolo Harbor, deposition velocity of aerosols, the nutrient concentrations in aerosols, and the solubility of each nutrient, while wet deposition is estimated by multiplying the area of the Tolo Harbor, precipitation rate, and nutrient concentrations in the rainwater. The dry deposition velocities for NH 4 + and NO x − in Tolo Harbor area are 0.03 and 0.12 cm/s, respectively (Wai et al, ). The concentrations of NH 4 + and NO x − in aerosols of Hong Kong are ~ 3042.2 ± 438.7 and 3781 ± 415.4 ng/m 3 according to the data from 2010 to 2016 (EPD, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ammonium depositions to the northern SCS were slightly lower than those measured over the YS, ECS, and WNP (15-30 mmol N m −2 year −1 ), but considerably lower than those in coastal areas of China (up to 100 mmol N m −2 year −1 ). Similarly, the observed NO − 3 and NH + 4 deposition fluxes in the northern SCS were relatively lower than those (35-212 mmol N m −2 year −1 for nitrate and 36-163 mmol N m 2 year −1 for ammonium) in coastal urban stations in southern China (Jia and Chen, 2010;Wai et al, 2010). Such a spatial pattern with an offshore decreasing tendency implies that N r (including nitrate and ammonium) was essentially transported from the continent via the northeasterly winds during the winter monsoon.…”
Section: Implications Of Atmospheric N R Deposition To the South Chinmentioning
confidence: 90%
“…Dry deposition is difficult to estimate and measurements are scarce in PRD. Wai et al (2010) reported dry deposition of NH þ 4 -N and NO À 3 -N measured at two Hong Kong Environmental Protection Department (EPD) sites (Central Western and Kwun Tong). The weekly dry deposition samples were collected by an automated wetÁdry sampler using a solid polyethylene as the surrogate surface.…”
Section: Comparison With Published Data In Prd Other Chinese Rapid-umentioning
confidence: 99%
“…Wai et al (2010) also compared the daily dry deposition measurements using a solid polystyrene surface and a water surface at an urban site in Hong Kong for about six months and found that the dry deposition fluxes of NH þ 4 -N and NO À 3 -N collected by water surface were about 14 and seven times those collected by the solid polystyrene surface, respectively. If applying these ratios to the Hong Kong EPD measurements (Wai et al, 2010), we find that Hong Kong had a closely comparable dry deposition flux of NH þ 4 -N, but a much higher dry deposition flux of NO À 3 -N than DHS and HM in this study. Table 3 presents the comparison of the annual dry deposition fluxes of reactive N in this study with the other sites in China and the other countries.…”
Section: Comparison With Published Data In Prd Other Chinese Rapid-umentioning
confidence: 99%